2013
DOI: 10.12968/bjnn.2013.9.4.172
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of the unpredictability of multiple sclerosis: a qualitative literature meta-synthesis

Abstract: Rose, Hannah and das Nair, Roshan (2013) The psychological impact of the unpredictability of multiple sclerosis: a qualitative literature meta-synthesis. British Journal of Neuroscience Nursing, 9 (4). pp. A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 28 publications
(40 reference statements)
1
40
0
Order By: Relevance
“…In line with a previous meta-syntheses (Wilkinson & das Nair, 2013), we used the Critical Appraisal Skills Programme tool (CASP, 2010) to assess the quality of included studies. The CASP can be used to assess studies employing various qualitative methods.…”
Section: No Interview/focus Group Datamentioning
confidence: 99%
“…In line with a previous meta-syntheses (Wilkinson & das Nair, 2013), we used the Critical Appraisal Skills Programme tool (CASP, 2010) to assess the quality of included studies. The CASP can be used to assess studies employing various qualitative methods.…”
Section: No Interview/focus Group Datamentioning
confidence: 99%
“…Qualitative studies also showed that as functional limitations increase in MS, people find it difficutl or impossible to identify new, fulfilling activities and they may give up efforts to adjust altogether (Lexell, Lund, & Iwarsson, 2009;Wilkinson & das Nair, 2013). Further, people (n=15) who perceived their MS as severe reported that they felt social excluded and were less willing to express their unmet needs (Galushko et al, 2014).…”
Section: Running Head: Adjustment In Progressive Msmentioning
confidence: 99%
“…Multiple sclerosis has an unpredictable disease course with a changing trajectory, causing difficulties in symptom management for both people with MS (PwMS) and clinicians (Deibel et al . , Wilkinson & das Nair , Davies et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis has an unpredictable disease course with a changing trajectory, causing difficulties in symptom management for both people with MS (PwMS) and clinicians (Deibel et al 2013, Wilkinson & das Nair 2013, Davies et al 2015. Historically, services for MS have been provided in hospital-based specialist clinics, and correspondingly research has focussed on patients' experiences of secondary care and the role of neurologists and MS Specialist Nurses (SNs).…”
Section: Introductionmentioning
confidence: 99%